Evaluasi Program Beasiswa Sepuluh Sarjana Per Desa Oleh Dinas Pendidikan Kabupaten Bojonegoro - Sofia Nur Oktaviani; Weni Rosdiana (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
The Ten Scholars per Village Scholarship Program (SESAR) is an initiative of the Bojonegoro Regency Government to expand access to higher education for rural communities. This study evaluates the implementation of the program using the CIPP model (Context, Input, Process, Product). The evaluation was conducted through interviews, document analysis, observations, and information from program implementers to assess policy relevance, resource readiness, process quality, and achieved outcomes. The results indicate that the program is relevant to the goal of educational equity; however, the distribution of beneficiaries has not been even due to differences in the number of applicants and socio-economic conditions among villages. In terms of context, the program aligns with the need for equitable access to higher education, although beneficiary distribution remains uneven. From the input perspective, regulations and funding are adequate, but administrative requirements and higher education accreditation criteria still limit potential applicants. Regarding the process, the selection mechanism follows the established guidelines; nevertheless, socialization remains insufficient, document verification poses challenges, and fund disbursement is often delayed. In the product aspect, the program provides tangible benefits by supporting the continuity of higher education for rural students, although its overall effectiveness still requires improvement.